FROM KONYA TO NUSANTARA: RUMI’S SUFI DIASPORA IN PIDIE, ACEH, INDONESIA - Fakhriati Fakhriati (Islam Futura, 2020)
Rumi’s Sufism has not only flourished in Turkey, where the sufi was born, but also in many other far-flung world regions such as Nusantara.  Its worldwide success invites many questions, for example, the reasons for its ability to attract both Muslims and non-Muslims. In Pidie, Aceh, Indonesia, one of its popular aspects is the sema ritual dance, which has spread to other Aceh sufi orders (tariqa), especially the Naqshbandi sufi order. This dance is an adaptation of foreign teaching and performance to local context in the location of the study, the village of Lampôh Saka in Pidie. Aceh’s sufi orders have succeeded in synthesizing foreign and local culture to create something uniquely their own. This study could offer an example of how to develop harmony and peace in Indonesian life, as exemplified by the sema dance, which symbolizes care towards creation while maintaining submission to the Creator.